Improving the Level of Economic Development and Social Welfare in Rural Areas for Young People - Jafarli, Fuad (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
One of the three global goals set by states is to eradicate poverty and ensure economic and social progress for all. Young people in many low- and middle-income countries face exceptional challenges in finding their place in a globalizing economy. Integrating hundreds of millions of young people into the labor market is one of the greatest global development challenges for decades to come. Rural populations all over the world are aging. The role of young people as drivers of change in agricultural and food systems and their place in rural labor markets is receiving increasing attention at the global level, especially as a result of increased global migration flows. How can this problem be transformed into a “youth” driving force for rural development? This paper argues for leveraging growing demand for agricultural products and recent advances in the agricultural sector to expand youth employment opportunities and promote attractive decent jobs, especially green jobs, in rural areas. The paper analyses the situation in our daily life, in which the proportion of the worldwide countries are dealing with the problem related to the economic development and social welfare in rural areas. The paper includes the following issues such as the attractiveness and creation of opportunities for youth and consideration of them as the main partners in rural areas play a crucial role nowadays. Moreover, green jobs as well are effective and efficient in enhancement of both productivity and sustainability of agricultural sphere. The question is how to transform this challenge into an opportunity and harness the energy of young people as a driving force for development. The role of young people as drivers of change in agro-food systems and their place in rural labor markets is receiving increasing attention at the global level, especially as a result of increased global migration flows. A top priority for developed and developing countries is to systematically mainstream youth rural decent employment issues into programs and investment projects in agriculture, value chains, agro-industry development, rural transformation, and sustainable food systems. This paper argues for expanding employment opportunities for youth through the creation of decent jobs, especially green jobs, in rural areas.